ASSESSING THE PUBLIC PERCEPTION AND TARGETED IMPLEMENTATION OF ELECTRIC MOTORCYCLES IN DENPASAR CITY RELATED TO EMISSION REDUCTION - Prasetyo, Otniel Stefen Adi; Sholihah, Qomariatus; Pangestuti, Edriana; Osawa, Takahiro; Prasetyo, Rahmadi (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 2 (2024)DO - 10.24843/EJES.2024.v18.i02.p10, 2024)
Using an electric motorcycles can contribute to decreasing emissions in the transportation sector. Government policies and various socialization programs have supported the development of electric vehicles. This research was conducted to determine the public perception and implementation of electric motorcycles in Denpasar City. The public perception was obtained through questionnaires and in-depth interviews with related key persons. The statistical analysis of the questionnaire indicated a good category with a score of 3.43. The level of community acceptance was influenced by quieter and environmentally friendly technology, electricity tax subsidies, and lower electric fuel costs. The interview with community and government representatives reinforced the public acceptance finding affected by the intensive public outreach program and a vehicle installment payment scheme. As the result, The implementation target was rated optimistic, with a potential CO2 emission reduction of up to 32,641 tons/year in 2026.  All the efforts to implement electric motorcycles in Denpasar City by the goverments have met the requirements to achieve acceptance of perceptions in the people of Denpasar City. This thing’s very important to reaching out the scenario of reducing CO2 emissions by 2026. In addition, it is important to have a more study regarding to the sustainability of the electric motorcycles ecosystem, such as the availability of data sources update from related agencies that show efforts to improve infrastructure by producers, the number of charging station and selling stations, as well as opportunities for domestic production and incentive policies. Keywords :      Electric Motorcycles; Emission; Implementation Targets; Level of Acceptance; Public Perception